Projected climate change impacts on crop yields in China's drylands by statistical models and emulators - Shuangshuang Zi; Yiqing Liu; Yan Li; Shuai Wang; Shan Sang; Huiqing Lin; Chengcheng Hou; Fengyu Fu; Bojie Fu (Agricultural Systems, 2026)

Phylogenomics and morphological evidence reveal a new genus Callibractia gen. Nov. (Apiaceae, Apioideae), a distinct alpine lineage of Sino-Himalaya shaped by uplift of the Pan-Tibetan Highlands - Zi-Xuan Li; Chang Peng; Xing-Jin He; Yu-Lin Xiao; Wei-Yan Tan; Li-Jia Liu; Song-Dong Zhou (Molecular Phylogenetics and Evolution, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Structure and bioactivity of protolimonoids from the root bark of Dictamnus dasycarpus Turcz. - Hua Yue; Zi-Xuan Li; Zi-Tong Hao; Dan Zeng; Jie Bao; Ling-Zhi Zhang; Xue-Man Lin; Hua Sun; Shu-Fang Li; Su-Juan Wang (Phytochemistry, 2026)

Persistence of a high-risk opportunistic pathogen amid compartment-resolved antibiotic resistance attenuation in acute shock-loaded micro-wetlands - Rong-min Zhang; Zi-yao Liu; Hui-ting Chen; Xin-ce Yang; Liwei Shi; Yi-cheng Zhang; Xin-ting Li; Lin-lin Yang; Jing-yu Xu; Xin-lei Lian; Li Li; Xian-hui Huang; et al. (Journal of Environmental Chemical Engineering, 2026)

Recoverable millimeter-sized poly(ether-ether-ketone)-based adsorbent beads with multisite complexation for Co2+/Ni2+ removal from radioactive wastewater - Peng-De Yu; Yan-Lin Ren; Wen-Juan Wang; Ya-Juan Cai; Ting Yue; Ke-Xiao Sang; Yi-Xing Sun; Dan Wu; Zi-Hao Yang; Chuan-Zhe Zhao; Ying-Kang Li; Ya-Ge Wu; et al. (Journal of Environmental Chemical Engineering, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Antagonistic effects of PM2.5 and ozone on respiratory morbidity: A multi-pollutant interaction analysis using outpatient data from China's Pearl River Delta - Shui-Yue Lu; Xue-Dan Xu; Dao-Qin Wang; Muhammad Amjad; Guang-Hui Dong; Li-Zi Lin; Hong-Wei Tu (Atmospheric Environment, 2026)

Schisandra chinensis polysaccharide attenuates diabetic islet cell injury by promoting autophagy via suppression of the PI3K/AKT/mTOR signaling cascade - Xiao-Ying Zhou; Guang-Hui Zhou; Wen-Chong Li; Jun-Feng Zhang; Ming-Kui Lin; Zi-Cong Liang; Rui-Ke Liu (Journal of Molecular Histology, 2026)

An integrated optimization framework for voyage and fleet allocation planning in Ro-Ro transport under multiple ship types and contract requirements - Chuanzhong Yin; Xinyi Yao; Luoyi Chen; Lin Li; Zi-Ang Zhang (Ocean Engineering, 2026)

Outdoor light at night, sleep disorder, and atopic diseases among children and adolescents: a cross-sectional study - Si-Han Wu; Le-Bing Wang; Xiao-Fan Lu; Yang-Yang Li; Joachim Heinrich; Lidia Morawska; Steve Hung Lam Yim; Shao Lin; Bin Jalaludin; Yi-Ran Chen; Xiao-Yi Liu; Yuan-Yuan Fan; et al. (International Journal of Hygiene and Environmental Health, 2026)

Seasonal variations in air-sea interface processes and water column biogeochemical regulation mechanisms of PAHs in the South China Sea - Jingwen Shi; Ye Li; Yina Tanli; Mengyang Liu; Yan Lin; Lin Zhang; Mingjun Feng; Hongwei Ke; Xiangrong Xu; Zi-Feng Zhang; Yi-Fan Li; Xuehong Zheng; et al. (Environmental Research, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Fire severity alters soil microbial diversity and community stability in a subtropical forest ecosystem - Yuan Tang; Tongjian Zi; Xiaona Li; Jiayao Zhang; Shuyi Lin; Yunjia Mo; Bin Tian; Xuezhao Wang (CATENA, 2026)

Removal of antibiotics by an oleaginous green microalga Chromochloris zofingiensis under photoautotrophic, heterotrophic and mixotrophic conditions - Kai-Lu Cao; Juan Peng; Meng-Zhen Li; Lin-Yun Liao; Zi-Wen Song; Hong-Zhi He; Jun Zhao (Algal Research, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Co-contamination of hybrid microplastics and PFOA/GenX alters rhizosphere bacterial–fungal communities and root performance of Eichhornia crassipes - Zu-lin Hua; Zi-wei Chen; Ye-bing Shi; Li Gu (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Seismic behavior of novel multi-celled composite shear walls with energy-dissipating corrugated steel plates - Dai-Jiang Zhou; Xian Li; Chen-Ze Li; Zi-Lin Zhang; Xi-Guang Liu; Ming Chen (Engineering Structures, 2026)

Structural characterization and in vitro evaluation of the hypolipidemic activity of the HSP-Ia, a bioactive polysaccharide derived from hemp (Cannabis sativa L.) seeds - Ya-Zhi Wang; Lan-Yan Li; Yong-Zhe Chen; Dong-Xue Song; Feng-Yu Liu; Zi-Yi Zhang; Hong-Lin Guo; Jun Li; Tao Liu; Chen-Feng Ji; Shou-Dong Guo (Carbohydrate Polymers, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Alnustone ameliorates obesity and polycystic ovary syndrome by remodeling adipose metabolism via AMPK signaling - Yiming Qin; Shourui Hu; Yanqi Xu; Zongxuan Lin; Xiaofan Liang; Yue Liu; Yuxuan Li; Chunxuan Geng; Xiangyan Chen; Xizi Feng; Zi-Jiang Chen; Han Zhao; et al. (Science China Life Sciences, 2026)

Is BPA only the tip of the iceberg? Occurrence and risk assessment of 32 bisphenol analogues in landfill leachate - Zhi-Zhong Zhang; Lin-Hui Zhang; Hang Li; Fei Chen; Sakhayana Nikolaevna Danilova; Ming-Han Li; Bing-Feng Liu; Yi-Fan Li; Zi-Feng Zhang (Journal of Hazardous Materials, 2026)

Individual and joint association between per- and polyfluoroalkyl substances and skeletal muscle among 6-9 years old children in China - Xue-Mei Liao; Li-Zi Lin; Wan-Ting He; Yun-Ting Zhang; Si-Hui Guo; Shu-Jun Liang; Zhen Hong; Zhe-Qing Zhang; Guang-Hui Dong; Qin-Zhi Wei (International Journal of Hygiene and Environmental Health, 2026)

Ultrastable Pt clusters confined on CeO2 nano-islands for efficient low-temperature propane dehydrogenation over carbon nanotube - Jian Tao; Shu-Lin Liu; Zi-Dan Li; Wan-Yi Wang; Chuan-Feng Huang; Bao-Lian Su; Zhao Wang (Chemical Engineering Journal, 2026)

Artificial cell-free pathway for carbon-efficient glycerol-HCO3− conversion to l-aspartate with ATP and cofactor trade-offs - Long-wei Lou; Zi-hang Xi; Zong-lin Li; Zhi-min Li (Bioresource Technology, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

Pseudostellaria heterophylla Extract Enhances the Immune Responses in Larimichthys crocea Against Pseudomonas plecoglossicida Infection - Kun Huang Han; Zi Min Li; Li Zhou; Dong Ling Zhang; Ying Li; Zhao Han Sun; Jia Chen; Zhi Deng Lin; Yan Bin Dai; Peng Fei Zou (Fishes, 2026)
Visceral white spot disease caused by Pseudomonas plecoglossicida poses a severe threat to large yellow croaker (Larimichthys crocea) aquaculture. This study investigated the immunomodulatory effects and underlying mechanisms of Pseudostellaria heterophylla extract against P. plecoglossicida infection in L. crocea. Fish were fed a basal diet supplemented with 1% P. heterophylla extract for 30, 45, and 60 days, followed by intraperitoneal injection with 200 μL P. plecoglossicida (1 × 104 CFU/mL). When the control group reached about 50% mortality, transcriptome sequencing of head kidney tissues was performed on the 45 and 60 days post-feeding of the treatment groups to analyze gene expression changes following bacterial infection. Survival rates of the treatment groups were 33.33%, 13.33%, and 20% higher than those of the control group at 30, 45, and 60 days post-feeding, respectively. Transcriptomic analysis revealed time-dependent transcriptional responses: in one group, 45 days post-feeding, 10 differentially expressed genes (DEGs) were identified (2 up-regulated and 8 down-regulated), whereas in another group, 60 days post-feeding, 893 DEGs were detected (417 up-regulated and 476 down-regulated). Functional enrichment analysis (GO, KEGG, and GSEA) demonstrated that DEGs were significantly enriched in immune-related pathways, including Toll-like receptor signaling, chemokine activity, Th1 and Th2 cell differentiation, hematopoietic cell lineage, and cytokine–cytokine receptor interaction. Key immune genes, including chemokines, Toll-like receptors, and T cell regulators, were significantly up-regulated. These findings indicate that P. heterophylla extract enhances both the specific and non-specific immune capabilities of L. crocea in a time-dependent manner, with prolonged supplementation eliciting more robust transcriptional activation of immune defense pathways. This study provides a scientific foundation for developing immunological prevention strategies against P. plecoglossicida infection in aquaculture.

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Chronic exposure to low-dose cadmium disrupts spermatogenesis in mice through ectoplasmic specialization damage - Yue Li; Zi-Fa Li; Bo Qiu; Kai Chen; Tian-Lin Zhang; Hai-Peng Wang; Lin Wang (Journal of Environmental Sciences, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Potential structure-immunostimulatory activity relationship of Tartary buckwheat sprout pectic polysaccharides: Influences of molecular mass and esterification degree - Bo Li; Lin Zhang; Ding-Tao Wu; Qin Yuan; Shengpeng Wang; Mao-Ling Tan; Mei-Lin Feng; Yi-Chen Hu; Liang Zou; Zi-Peng Wang; Ya-Nan Cao; Jing-Wei Huang (Food Research International, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Geometry-matched chelation enhances Li+ diffusion on electrodes binded by modified carboxymethyl cellulose - Zi Ye; Xi Yang; Wenhan Chen; Xinye Li; Yu Chen; Ning Yu; Jin Huang; Lin Gan (Carbohydrate Polymers, 2026)

Hydrogeochemical Characteristics and Potential Risks within a Headwater Catchment, Taihu Lake Basin, China - Lin Liu; Hai Yang; Xun Zhou; Yuehua Jiang; Naizheng Xu; Jiangshi Gong; Zi Chen; Liang Li; Jinsong Lü; Yang Jin (Journal of Earth Science, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Characteristics of structural superimposed halo at the Jiawula Ag-Pb-Zn deposit, Inner Mongolia, China and its significance for exploration - Xin-yu Gao; Gui-yuan Sun; Kang Wang; Wei Zhang; Zhi-ping Li; Wen-ju Li; Jiang Wei; Lin Yang; Hong-zhe Xie; Zi-wen Yang; Chao Ma (Journal of Geochemical Exploration, 2026)

Wnt signaling dysregulation drives Stargardt disease pathogenesis - Xiao Zhang; Zhuo-Lin Liu; Xiao Lin; Shu-Ning Sun; Dandan Shi; Lu Tian; Yang Li; Zi-Bing Jin (Science China Life Sciences, 2026)

Electroplating parks as hidden sources of novel plastic additives: Occurrence, migration pathways, and ecological risks - Zi-Tong Li; Zecong Ding; Yingjie Chen; Kai Cui; Li Wang; Hai-Yan Zhang; Qian Jiang; Li-Qian Lin; Jian-Liang Zhao (Water Research, 2026)

Fermented red quinoa (FRQ) effectively mitigates chronic alcohol-induced cognitive impairment and hepatic steatosis through multi-mechanistic pathways - Zi-Han Lin; Zhaohui Wang; FenFen Wei; Xinyao Zhu; Junwei Ma; Yan Wu; Song-Mei Chen; Li-Hua Song (Food Research International, 2026)

Co-solvent-modulated polyamide nanofiltration membranes for high-temperature separation - Wan-Long Li; Xiao-Wei Luo; Wan-Ting Lin; Si-Yuan Zhang; Zi-Lu Zhang; Zi-Jun Zhang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2026)

Integrated dynamic control and enzyme co-localization strategies enable high-efficiency stilbenoid biosynthesis - Guofu Zhao; Pengpai Li; Xinyao Ding; Jiugong Lv; Ying Yang; Lin Liu; Lihan Zi; Qiang Zhang; Liya Liang; Rongming Liu (Bioresource Technology, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

In-situ reactivation of the catalyst for hydrodeoxygenation of bio-oil to biofuel by coupling the self-rotation and revolution of catalysts in the swirling flow - Yao Zhang; Zheng-hao Yang; Yu-long Chang; Jian-ping Li; Bang-da Wang; Zi-heng Jin; Liang Ma; Xia Jiang; Hua-lin Wang (Journal of Cleaner Production, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

High-resolution seismic data processing based on low-dimensional manifold constraints - Gang-lin Lei; Guang-liang Zhao; Suo Cheng; Yang Tan; Jiang-wei Shang; Ze-lin Li; Zi-lun Xiong; Zhu-kun Wang (Applied Geophysics, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Enhanced fluoxetine removal from water via Fe/Cu-doped biochar-activated percarbonate under sunlight and aeration - Yang Wu; Zhi-hao Li; Xi-xi Lu; Zi-xuan Lin; Chang-ping Yu (Journal of Environmental Chemical Engineering, 2026)

Structural characteristics and bioactivities of an exopolysaccharide from mycelial fermentation of a medicinal fungus Cs-HK1 - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2026)

Submerge-emerge alternation regulates per(poly)fluoroalkyl substance fate in emergent plants: Insights from growth, physiology, and metabolomics - Ye-bing Shi; Zu-lin Hua; Zi-wei Chen; Xiao-qing Li; Li Gu (Aquatic Toxicology, 2026)

Comprehensive evaluation and analysis of cold tolerance in Neopyropia yezoensis strains based on multiple traits - Zi-Xiang Zhai; Guo-Ying Du; Lan Wu; Lin Tian; Li-Hong Ma (Aquaculture, 2026)

Enhancing bentonite slurry with sodium alginate for subsea tunnelling: rheological behavior, infiltration, and filter cake characteristics - Hong-tao Cao; Shan-lin Xu; Ji Xie; Jiang Liu; Hong-lei Sun; Zi-li He (Tunnelling and Underground Space Technology, 2026)

Eight previously undescribed flavonoids and four previously undescribed bibenzyls from Macaranga kurzii and their potential antiviral activities - Yan-Zi Ma; Ding-Cheng Zhang; Liu Yang; Xue-Wen Wu; Bo Li; Muhammad Aurang Zeb; Yuan-Lin Kong; Xue-Mei Zhou; Wei-Lie Xiao; Chang-Bo Zheng; Xiao-Li Li (Phytochemistry, 2026)

Mechanisms of Cr (VI) reduced by nitrogen-fixing bacteria - Zi-Xiao Xue; Han-Lin Gu; Zi-Yi Mu; Yun Niu; Meng-Die Li; Zhuo Lu; Wei Zhang (Journal of Hazardous Materials, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Novel senescence inducer ICA-11c, a derivative of icaritin, YAP-dependently suppresses hepatocellular carcinoma cells - Hong-fei Chen; Shuai Shen; Shuang-li Wang; Li Ye; Ji-chong Li; Wen-li Cao; Zi-lin Hou; Jian-huan Jia; Qing-bo Liu; Guo-dong Yao; Shao-jiang Song (Chemico-Biological Interactions, 2026)

Brain Tissue-Derived Exosomal Proteomics Identifies Chemotaxis-Associated Protein Changes After Traumatic Brain Injury: An Exploratory Hippocampal Transcriptomic Comparison - Wei-can Chen; Xin-li Chen; Cheng-ye Lin; Yang-zi Huang; He-fan He; Yi-lin Zhou; Yi-bin Liu (Molecular Neurobiology, 2026)

Field and laboratory investigations of the fluid in fully developed debris flows - Xiao Su; Ze-Min Xu; Yi-Xi Wen; Bin Li; Jing-Kai Meng; Lin Tian; Zi-Ming Ye; Gui-E Shi (Bulletin of Engineering Geology and the Environment, 2026)

Whether the hybridization of polystyrene, polyethylene, and polypropylene microplastics impacts aquatic carbon leakage from water hyacinth: A case study considering per(poly)fluorocarboxylicacid cocontamination - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Chun Wang (Journal of Environmental Chemical Engineering, 2025)

Drivers of protistan communities in a subtropical coastal wetland: roles of plant types and soil depths - Zi-Kai Liu; Lu Li; Bowen Huang; Luhong Zhou; Yongxin Lin; Ping Yang; Ju-Pei Shen; Weidong Chen (CATENA, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

MST1 modulates inflammatory responses by targeting the NF-κB/NLRP3 pathway in LPS-induced acute lung injury - Zi-xi Peng; Lin-li Song; Xiao-Li Wang (Histochemistry and Cell Biology, 2025)

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Microplastic contamination in waterbirds and their habitats: evidence from little egrets (Egretta garzetta) in tropical rice fields - Han-xun Qiu; Chuan-biao Xu; Xin Huang; Xiang-yin Wei; Zi-lin Pang; Lan-fang Du; Li Jiang; Ji-liang Zhang (Environmental Research, 2025)

Humid heat’s nonlinear impact on school-age children’ sleep health: Evidence from Guangdong, China - Yuan Gao; Li-Zi Lin; Wen-Wen Bao; Wan-Ting He; Yun-Ting Zhang; Guang-Hui Dong; Shenjing He (Environmental Research, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Marine Hydrogen Pressure Reducing Valves: A Review on Multi-Physics Coupling, Flow Dynamics, and Structural Optimization for Ship-Borne Storage Systems - Heng Xu; Hui-Na Yang; Rui Wang; Yi-Ming Dai; Zi-Lin Su; Ji-Chao Li; Ji-Qiang Li (Journal of Marine Science and Engineering, 2025)
As a zero-carbon energy carrier, hydrogen is playing an increasingly vital role in the decarbonization of maritime transportation. The hydrogen pressure reducing valve (PRV) is a core component of ship-borne hydrogen storage systems, directly influencing the safety, efficiency, and reliability of hydrogen-powered vessels. However, the marine environment—characterized by persistent vibrations, salt spray corrosion, and temperature fluctuations—poses significant challenges to PRV performance, including material degradation, flow instability, and reduced operational lifespan. This review comprehensively summarizes and analyzes recent advances in the study of high-pressure hydrogen PRVs for marine applications, with a focus on transient flow dynamics, turbulence and compressible flow characteristics, multi-stage throttling strategies, and valve core geometric optimization. Through a systematic review of theoretical modeling, numerical simulations, and experimental studies, we identify key bottlenecks such as multi-physics coupling effects under extreme conditions and the lack of marine-adapted validation frameworks. Finally, we conducted a preliminary discussion on future research directions, covering aspects such as the construction of coupled multi-physics field models, the development of marine environment simulation experimental platforms, the research on new materials resistant to vibration and corrosion, and the establishment of a standardized testing system. This review aims to provide fundamental references and technical development ideas for the research and development of high-performance marine hydrogen pressure reducing valves, with the expectation of facilitating the safe and efficient application and promotion of hydrogen-powered shipping technology worldwide.

Tight sandstone reservoirs in lacustrine environments: review and perspectives - Chen-Lin Hu; Zi-Qiang Lin; Xin Li; Jonathan Atuquaye Quaye; Zhi-Qiang Fu (International Geology Review, 2025)

Corrigendum to ‘Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A’ [Phytochemistry. 222 (2024) 114073] - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li Ping Lin (Phytochemistry, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Mulberry (Morus alba L.) planting increased the abundance of soil carbon cycling functional genes by improving soil properties, and further enhanced the stability of soil carbon pool - Meina Zhu; Zi Yang; Zhenjiang Wang; Victor Edem Tsigbey; Zipei Cui; Wenfeng Zhang; Weijun Zhu; Jianbin Li; Changyu Qiu; Qiang Lin; Haonan Li; Hanfa Shahid; et al. (Plant and Soil, 2025)

Age-stage, two-sex life table, and host plant selection behavior of the aphid Myzus persicae (Sulzer) (Hemiptera: Aphididae) on three Brassica juncea cultivars and one Brassica rapa cultivar - Mi Tian; Lin-kui Li; Zi-hua Yang (Arthropod-Plant Interactions, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Coffee mitigated cognitive impairments in sleep-deprived mice by regulating circadian rhythm, inflammation, oxidative stress, and intestinal ecology - Hui-Bin Jiang; Fen-Fen Wei; Wen-Ting Li; Zi-Han Lin; Chuang Zhu; Yan Wu; Ying Wang; Li-Hua Song (Food Bioscience, 2025)

Revolutionizing plasma sprayed LSCF cathodes: Fe-induced phase restoration and enhanced electrochemical performance for high-efficiency SOFCs - Zi-Yang Chen; Xin Zhang; Yan-Neng Liang; Jiu-Tao Gao; Shan-Lin Zhang; Chang-jiu Li; Cheng-Xin Li (Chemical Engineering Journal, 2025)

From AI to action: Antimicrobial peptides engineered by generative adversarial networks (GANs)-A novel approach to combat resistant Bacteria - Chia-Wen Lai; Chung-Yen Lin; Meng-Chen Tsai; Wei-Jung Chen; Chia-Chun Hsieh; Zi-Jing Lin; Li-Jiuan Shen; Ying-Lien Chen; Lee-Jene Lai; Shu-Hwa Chen; Yang-Hsin Shih (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

GMNN mutations cause female infertility characterized by preimplantation embryo arrest through regulating DNA re-replication - Honghui Zhang; Wei Su; Xiaohong Jiang; Yang Wang; Bohan Yang; Xian Wan; Cheng Li; Shuai Zhao; Changlong Zhang; Shigang Zhao; Yuehong Bian; Mei Li; et al. (Science China Life Sciences, 2025)

Juvenile macular degeneration in nonhuman primates generated by germline knockout of ABCA4 gene - Ya Ma; Qiang Lin; Hai-Long He; Yi-Xin Liu; Min Li; Xiao-Hui Zhang; Zi-Bing Jin (Science Bulletin, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

The Interplay Between Climate Warming Driven by Greenhouse Gas Emissions and the Ecotoxicological Effects of Microplastics: Insights From a Meta‐Analysis - Xinyan Lv; Aijun Lin; Xuedan Cui; Yanqi Li; Zi Guo; Xiao Tan; Guilan Duan (Global Change Biology, 2025)
An increasing number of studies have revealed the interconnections and interactions between global warming and microplastics. However, research in this field is still in its early stages, with fragmented content and inconsistent conclusions. Therefore, this paper adopts a meta‐analysis method to summarize and analyze the relevant literature in this area. After screening, a total of 39 research papers and 730 data points related to the interactions between global warming and microplastic pollution were obtained. The research results indicate that, on one hand, soil microplastic pollution significantly increases greenhouse gas CO 2 emissions by 140.20%, N 2 O emissions by 195.27%, and Global Warming Potential by 172.10%, thereby exacerbating global warming. By introducing explanatory variables for analysis, it was found that microplastic type, soil type, and soil dissolved organic carbon are important influencing factors. On the other hand, the study also explains that the rise in water temperature due to global warming amplifies the biological toxicity effects of microplastics, leading to oxidative damage and poisoning in aquatic animals. The bidirectional interaction mechanism between microplastic pollution and global warming may form a vicious cycle, further increasing the vulnerability of ecosystems. This study provides a theoretical basis and research direction for addressing the dual threats of microplastic pollution and global warming.

Potential viral influence on sulfur metabolism in acid sulfate soils - Li Bi; Shuai Du; Rob Fitzpatrick; Qing-Lin Chen; Thi Bao-Anh Nguyen; Zi-Yang He; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Maillard reaction products derived from xylose-phosphatidylethanolamine: Potential anti-oxidative substances from hot-pressed flaxseed oil - Yi-kang Zhang; Ke-yao Li; Yue Du; Lin Wang; Qian Xiong; Ning Zhang; Xin Yue; Jia-zi Chen; Martin J.T. Reaney; Yong Wang; Zi-zhe Cai (Food Chemistry, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Unveiling insecticidal compounds from the invasive weed Tithonia diversifolia against Spodoptera litura and elucidating mechanisms via transcriptomic analysis - Zhandi Wang; Xiaocui Zhuang; Kaixiang Chao; Yanping Li; Lin Jia; Caiyun Zi; Yuanqing Zhou (Pesticide Biochemistry and Physiology, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Reduction-stabilization characteristics, long-term stability and biotoxicity evaluation of Fe(II)/Al layered double hydroxides on Cr(VI) in contaminated soil - Xiao Tan; Qi Liu; YanQi Li; Xinyan Lv; Zi Guo; Guilan Duan; Aijun Lin (Environmental Pollution, 2025)

Reliable electrochemical ratiometric sensing based on diazotization/Schiff base reaction for accurate detection of alpha-fetoprotein - Miao Wang; Xing-Yu Liu; Lin-Xiao Zhao; Zi-Wen Cui; Shan-Shan Li (Chemical Engineering Journal, 2025)

Two-photon polymerization 3D printing of biomimetic microstructures for functionalizing surfaces to inhibit bacterial growth - Wentao Zhu; Fang-Yi Huo; Lei-Ming Cao; Zi-Zhan Li; Qian Zhu; Rongxiang He; Bolei Chen; Yong Liang; Bo Cai; Hong He; Lin-Lin Bu; Ligang Hu (Chemical Engineering Journal, 2025)

Mo isotope evidence for the significance of subducted continental crust in formation of post-collisional porphyry Cu deposits - Jing Jing Fan; Qiang Wang; Xiao Ping Long; Derek A. Wyman; Andrew C. Kerr; Jie Li; Zi Long Wang; Lin Gong; Dong Jing Xu; Qi Ji Yang; Le Zhang; Ze-Xian Cui (Chemical Geology, 2025)

Accelerated detection of carbapenem resistance in Klebsiella pneumoniae via single-cell Raman spectroscopy - Jia-Cheng Ding; Li-Ting Dai; Jia-Xin Tang; Hui-Min Zhang; Le-Le Zhai; Chuang-Ye Cai; Zhi-Rou Xiao; Zhe-Mei Chen; Jia-Hui Ling; Meng-Xue Zou; Xi-Wu Cao; Li-Juan Lin; et al. (World Journal of Microbiology and Biotechnology, 2025)

Greenspace and respiratory diseases and symptoms in Chinese children: A large-scale study exploring joint associations with ozone - Pei-Pei Dong; Gongbo Chen; Yue Wen; Joachim Heinrich; Elaine Fuertes; Tianyu Zhao; Nur Sabrina Idrose; Li-Zi Lin; Zhao-Huan Gui; Xiaodi Qin; Hongwei Tu; Guang-Hui Dong (Sustainable Cities and Society, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Using waste to treat waste: Coupling of advanced reduction processes and anaerobic fermentation - Xing-Yuan Chen; Yun Niu; Lin Pan; Han-Lin Gu; Wei Gao; Zi-Yi Mu; Li-Li Hu; Wei Zhang (Journal of Water Process Engineering, 2025)

The modifying role of residential greenness on the association between heat waves and adverse birth outcomes: Results from the ELEFANT project - Yuxuan Ma; Yuanyuan Yu; Lei Zhao; Qisijing Liu; Jiayan Ni; Zi Lin; Bin Chen; Weixia Li; Huishu Lin; Yuhong He; Shuhao Shi; Jianqiong Zheng; et al. (Environmental Research, 2025)

Late Mesozoic Wangxiang Composite Granitic Pluton, South China Block: Implications to Magma Emplacement and Evolution from Geochemical Proxies - Quan Ou; Jing-Yi Liu; Feng Zi; Bruna B. Carvalho; Xiaoping Long; Jian-Qing Lai; Kun Wang; Zi-Qi Jiang; Yi-Zhi Liu; Zheng-Lin Li; Hong-Yun Wang (Journal of Earth Science, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Synthesis of phosphorylated covalent organic frameworks with different linkages–Critical factors controlling the extraction of uranium from highly acidic media - Xiao-Yi Tang; Hui-Di Zhang; Zi-Jie Li; Shuai Wang; Si-Yan Liu; Tao-Yuan Xiu; Ji-Pan Yu; Lin Wang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Correction to: Scorpion Venom Heat-Resistant Peptide is Neuroprotective Against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2025)

Corrigendum to “Platelet-rich plasma/chitosan/chondroitin sulfate immunomodulatory hydrogel co-networks for diabetic wound repair: Functions and molecular mechanisms” [Chem. Eng. J. 491 (2024) 152138] - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2025)

Metabolic outcomes of Cordyceps fungus and Goji plant polysaccharides during in vitro human fecal fermentation - Fang Ting Gu; Jun Hui Li; Zi Chen Zhao; Yan Yu Zhu; Lin Xi Huang; Jian Yong Wu (Carbohydrate Polymers, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

In-situ forming flame-retardant gel polymer electrolyte through Ritter reaction: An innovative strategy for enhancing the safety of lithium metal battery - Si-Xin Jia; Tian-Qi Xiang; Zi-Han Zhang; Jian-Jun Zhou; Lin Li (Chemical Engineering Journal, 2025)

Transcriptome analysis of tilapia streptococcus agalactiae in response to baicalin - Qing-Qin Huang; Shao-Long Liu; Ji-Hui Huang; Fei Wang; Zi-Chen Zhao; Heng-Wei Deng; Chuan Lin; Wei-Liang Guo; Zhi-Hong Zhong; Jian-Long Li; Dong-Dong Zhang; Shi-Feng Wang; et al. (Genes & Genomics, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

Lignanamides: A comprehensive review of chemical constituents, biological activities, extraction methods and synthetic pathway - Jing Sun; Li-Tao Tong; Peng-Fei Tu; Lin-Lin Chen; Xin Xu; Ya Song; Xin-Xin Yang; Zi-Bin Guo; Xiang Zou; Chen-Xin Sun; Yan Mi; Bei Fan; et al. (Food Chemistry, 2024)

Bifidogenic properties of polysaccharides isolated from mushroom Lentinula edodes and enhanced immunostimulatory activities through Bifidobacterial fermentation - Lin Xi Huang; Fang Ting Gu; Yan Yu Zhu; Zi Chen Zhao; Jun Hui Li; Jian Yong Wu (Food Bioscience, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Bioaccessibility and bioavailability assessment of cadmium in rice: In vitro simulators with/without gut microbiota and validation through in vivo mouse and human data - Fei-Fei Xu; Ying-Si Chen; Xiu-Qin Lin; Ai-Hua Zhong; Min Zhao; Yue-Qi Li; Zi-Yin Li; Yue-Fei Lai; Jia Song; Jia-Liang Pan; Zhan-Fan Cai; Xu-Xia Liang; et al. (Science of The Total Environment, 2024)

Long-term exposure to ozone and sleep disorders in children: A multicity study in China - Zhao-Huan Gui; Joachim Heinrich; Lidia Morawska; Tian-Yu Zhao; Steve Hung-Lam Yim; Xiang-Qian Lao; Meng Gao; Duo-Hong Chen; Hui-Min Ma; Li-Zi Lin; Ru-Qing Liu; Guang-Hui Dong (Environmental Research, 2024)

Intrauterine exposure to long-chain perfluorocarboxylic acids (PFCAs) were associated with reduced primary bile acids in three-year-old children: Findings from a prospective birth cohort study - Yu-Ting Guo; Jin-bo Huang; Jing-chuan Xue; Shuang-Jian Qin; Dan Cai; Qi-Zhen Wu; Chu Chu; Cui-lan Tang; Yan-qi Xie; Li-Zi Lin; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2024)

Leaching-readsorption of VO43− optimized diffusion and adsorption of OH− on NiFeOOH catalytic interface for industrial water oxidation - Yu Ma; Mei-Xin Lin; Peng-Ji Su; Zi-Yi Gao; Xin Li; You-He Wang; Lian-Ming Zhao; Yong-Ming Chai; Bin Dong (Chemical Engineering Journal, 2024)

Optimizing iodine adsorption in functionalized metal-organic frameworks via an unprecedented positional isomerism strategy - Zi-Jian Li; Juejing Liu; Guangtao Zhang; Chris Benmore; Linjuan Zhang; Xiaofeng Guo; Jian Lin (Chemical Engineering Journal, 2024)

Robust self-healing ion-conductive interlocking dual-network binder based on gradient dynamic bonding for advanced SiO anodes in Li-Ion batteries - De He Weng; Liu Zhen Wu; Zi Feng He; Dong Yu Zhu; Yuan Li; Bole Ma; Qiyu Liu; Liheng Chen; Zhan Lin; Xueqing Qiu (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Simulated human digestion and fermentation of a high-molecular weight polysaccharide from Lentinula edodes mushroom and protective effects on intestinal barrier - Jun Hui Li; Fang Ting Gu; Ye Yang; Zi Chen Zhao; Lin Xi Huang; Yan Yu Zhu; Shiguo Chen; Jian Yong Wu (Carbohydrate Polymers, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

A One-Nano MOF-Two-Functions Strategy Toward Self-healing, Anti-inflammatory, and Antibacterial Hydrogels for Infected Wound Repair - Ya-Ling Fan; Hong-Jie Liu; Zi-Li Wang; Zi-Lin Wang; Li-Li Zhu; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

A nanoenzyme reactor fueled by a High-Glucose microenvironment for augmented diabetic tumor therapy - Zhi-Chao Hu; Hong-Jun Zhuang; Li-Yi Zhang; Qian Tang; Zhe Liu; Zi-Hao Lin; Ruo-Tao Liu; Zi-Yi Wang; Xiao-Hui Chen; Zhen-Zhong Zhu; Tao Yi; Li-Bo Jiang (Chemical Engineering Journal, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Distribution of soil tardigrades as revealed by molecular identification across a large-scale area of Australia - Zi-Yang He; Hang-Wei Hu; Bao-Anh Thi Nguyen; Qing-Lin Chen; Anthony Weatherley; Michael Nash; Li Bi; Keren Wu; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Tracing residual patterns and microbial communities of pharmaceuticals and personal care products from 17 urban landfills leachate in China - Lin-Hui Zhang; Jin-Nong Li; Yi-Hao Li; Xi-Ze Min; De-Yong Kong; Yue Han; Chao Jiang; Hang Xiao; Bin Liang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

Influence of SphK1 on Inflammatory Responses in Lipopolysaccharide-Challenged RAW 264.7 Cells - Chao-shun Wei; Lin-li Song; Zi-xi Peng; Xiao-Li Wang (Cell Biochemistry and Biophysics, 2024)

Prevention and control strategies for antibiotic resistance: from species to community level - Yan-Zi Wang; Hu Li; Qing-Lin Chen; Ting Pan; Yong-Guan Zhu; Dirk Springael; Jian-Qiang Su (Soil Ecology Letters, 2024)

Colletotrichum cliviicola as a new causal agent causing leaf spot disease on Tilia tomentosa moench (silver linden) in China - Lin Chang; Xue-hai Li; Yi-lin Li; Zi-wen Gao; Yue-mei Zhang; Ning-Li; Zhao-lei Qu; Yi-hong Yang; Hui Sun (Crop Protection, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Strengthened oil-water separation by swirl vane hydrocyclone based on short-circuit flow regulation - Wei Zhao; Jian-ping Li; Tong Zhang; Aosong Wei; Shi-yun Li; Zi-heng Zhao; Xue-jing Yang; Xia Jiang; Hua-lin Wang (Journal of Water Process Engineering, 2024)

Effective and selective recovery of Au(III) from WPCBs using quaternary phosphonium adsorbent synthesized by adjusting steric hindrance - Xinrong Li; Shuliang Chen; Peng Yang; Yue Lin; Chen Chen; Xianzhi Hu; Futing Zi (Journal of Hazardous Materials, 2024)

Analysis of proteomics and in silico allergenicity prediction of soluble proteins in selenium-enriched peanut leaves - Qi Gao; Wei-Xuan Li; Zi-Heng Liu; Mei Tie; Xue-Jun Gu; Masaru Tanokura; You-Lin Xue (Food and Bioproducts Processing, 2024)

Taxonomy and phylogeny of three species in Perichaena sensu lato (Myxomycetes = Myxogastria) from China - Wen-Long Song; Min Li; Zi-Qi Wang; Shuang-Lin Chen (European Journal of Protistology, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Two-photon polymerization-based 3D micro-scaffolds toward biomedical devices - Wei Wang; Zi-Qing Chen; Bin Lin; Mei-Chen Liu; Yang Zhang; Shu-Juan Liu; Yang Li; Qiang Zhao (Chemical Engineering Journal, 2024)

Elucidation of the beneficial role of co-fermented whole grain quinoa and black barley with Lactobacillus on rats fed a western-style diet via a multi-omics approach - Zi-Han Lin; Ling-Yue Zhong; Hui-Bin Jiang; Chuang Zhu; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Research International, 2024)

Platelet-Rich Plasma/Chitosan/Chondroitin sulfate immunomodulatory hydrogel Co-Networks for diabetic wound Repair: Functions and molecular mechanisms - Zi-Lin Wang; Lin-Yue Li; Hong-Jie Liu; Ya-Ling Fan; Yu-Xue Shen; Fei Song; Li-Li Zhu (Chemical Engineering Journal, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Isolation of undescribed cladosporols and spirobisnaphthalenes from a plant pathogen Cladosporium cladosporioides F-10-2-A - Peng Li; Zi Jin Zhang; Yu Tong Guo; Jing Guan; Lin Bo Wen Xi; Li-Ping Lin (Phytochemistry, 2024)

Continuous selenite biotransformation and biofuel production by marine diatom in the presence of fulvic acid - Hui-Ying Xu; Ruo-Yu Li; Zi-Qiang Yang; Jia-Fan Qiu; Yu-Bin Su; Carol Sze Ki Lin; Wei-Dong Yang; Hong-Ye Li; Jian-Wei Zheng; Xiang Wang (Bioresource Technology, 2024)

Effectively adsorb Au(S2O3)23− using aminoguanidine as trapping group from thiosulfate solutions - Yihuai Yang; Xianzhi Hu; Futing Zi; Shuliang Chen; Li Zhao; Xinrong Li; Yue Lin (Environmental Science and Pollution Research, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Degradation of prometryn during UV/persulfate process: Kinetics and disinfection by-product formation - Chen-Yan Hu; Hao Liu; Ling Xu; Yi-Li Lin; Qiang-Bing Wang; Dan-Dan Huang; Yi-Hui Wu; Zi-Yi Dong; Sheng-Jie Ji (Journal of Water Process Engineering, 2024)

The polyphenols profile of co-fermented quinoa and black barley with Lactobacillus kisonensis and its in vitro bioactivities - Hui-Bin Jiang; Pan Nie; Zi-Han Lin; Chuang Zhu; Ling-Yue Zhong; Fen-Fen Wei; Yan Wu; Li-Hua Song (Food Bioscience, 2024)

PM2.5 exposure-induced senescence-associated secretory phenotype in airway smooth muscle cells contributes to airway remodeling - Pei-Pei Cheng; Fan Yu; Shuai-Jun Chen; Xiao Feng; Zi-Heng Jia; Shi-He Hu; Xiao-Lin Cui; Ya-Ya Zhou; Qian Niu; Li-Mei Liang; Meng Wang; Lin-Jie Song; et al. (Environmental Pollution, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

The associations of secondhand smoke exposure with neurodevelopmental disorders and critical time window identification: A systematic review and meta-analysis - Xiao-Xuan Ou; Xin Wang; Xiao-Ling Zhan; Shu-Li Shen; Shamshad Karatela; Jin Jing; Li Cai; Ru-Qing Liu; Li-Zi Lin; Guang-Hui Dong (Science of The Total Environment, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Numerical investigation of a semi-submersible platform interacting with steep waves using a fully nonlinear method - Zi-Lin Zhang; Shi-Li Sun; Bo-Yu Chen; Hui-Long Ren (Ocean Engineering, 2024)

Bi-directional prediction of hydrothermal carbonization characteristics of agroforestry and livestock wastes with variable components: Graph learning model-aided waste recycle - Zi-Kai Lin; Chao-Sheng Li; Rong-Rong Cai; Yan-Qiu Long (Journal of Cleaner Production, 2024)

Highly efficient and selective extraction of Au(I) from thiosulfate gold-leaching solution using diphenylphosphine - Xinrong Li; Li Zhao; Shuliang Chen; Yue Lin; Xianzhi Hu; Futing Zi (Journal of Environmental Chemical Engineering, 2024)

Incorporating photocatalytic fuel cell with dual S-scheme CuBi2O4/Bi2WO6/ZnO NRA photoanode for energy recuperation from municipal wastewater treatment under sunlight - Zi-Jun Yong; Sze-Mun Lam; Jin-Chung Sin; Abdul Rahman Mohamed; Honghu Zeng; Haixiang Li; Hua Lin; Liangliang Huang; Jun-Wei Lim (Journal of Environmental Chemical Engineering, 2024)

Sustainable paramylon production from food waste by Euglena gracilis using a waste-based cell immobilisation technique - Jin-Hua Mou; Si-Fen Liu; Li-Li Yang; Zi-Hao Qin; Yu-Feng Yang; Zhen-Yao Wang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2024)

First report of Epicoccum latusicollum causing leaf spot disease on red maple (Acer rubrum L.) in China: Insights from a sentinel planting garden - Lin Chang; Yi-lin Li; Zi-wen Gao; Pierluigi (Enrico) Bonello; Michelle Cleary; Isabel A. Munck; Alberto Santini; Hui Sun (Crop Protection, 2024)

Generation and origin of persistent high excess pore water pressure in debris flows - Zi-Ming Ye; Ze-Min Xu; Bin Li; Xiao Su; Gui-E Shi; Jing-Kai Meng; Lin Tian (Geomorphology, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Response of distributions and emissions of summer biogenic sulfur in the Pacific Arctic to enhanced Pacific Water inflow - Cheng‐Xuan Li; Bao‐Dong Wang; Kan Chen; Gui‐Peng Yang; Jian‐Fang Chen; Li‐Na Lin; Zi‐Cheng Wang (Limnology and Oceanography, 2024)
The inflow of warm and nutrient‐rich Pacific Water (PW) through the Bering Strait into the Arctic Ocean is likely to have far‐reaching consequences for the ecosystem and biogenic sulfur cycle in the Earth's sensitive subarctic–arctic region of the Pacific sector, even impacting climate change under global warming scenarios. We performed a detailed biogeochemical study of summer biogenic sulfur cycling from cold (2012) to warm (2014) years in the Bering Strait and the Chukchi Sea, so as to highlight the importance of enhanced Pacific inflow in driving dimethylsulfide (DMS) variability. In the Bering Strait, the enhanced Pacific inflow led to the vertical expansion of the eastern high‐DMS regions due to the vertical extension of Alaska Coastal Water, and the horizontal expansion of the western surface high‐DMS regions due to the westward intrusion of Bering Shelf Water. The enhanced extension of PW potentially stimulated seawater warming, the northward retreat of the ice edge, and the enlargement of sea ice‐free areas in the Chukchi Sea. The northern ice melting zone at 71°N with a bloom of phytoplankton was an area of locally high dimethylsulfoniopropionate concentrations and slow DMS consumption in 2012. A hotspot for dimethylated sulfur compound concentrations and DMS sea–air flux occurred in the convergence region near 67.7°N during 2014, due to enhanced mixing caused by increased Bering Sea Water. Owing to the increased advection of PW during 2012–2014, surface DMS and its emission to the atmosphere increased sharply by threefold in the Chukchi Sea.

Structurally diverse terpenoids from Elephantopus scaber L. and their acetylcholinesterase inhibitory activities - Jia-Yi Li; Shu-Hui Dong; Xin Zhang; Zi-Jian Liu; Jin-Le Hao; Bin Lin; Ming Bai; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Limonoids from the roots of Melia azedarach and their anti-inflammatory activity - Min Song; Hui-Juan Luo; Zi-Wei Li; Ling Qiu; Yu-Xin Zhao; Cheng-Wei He; Xiao-Qi Zhang; Wen-Cai Ye; Li-Gen Lin; Qing-Wen Zhang (Phytochemistry, 2023)

Spatial bandgap tailoring via a novel injection chemical bath deposition enables highly efficient carbon-based Sb2(S,Se)3 thin film solar cells - Peng Tang; Zi-Heng Huang; You-Xian Chen; Hu Li; Li-Quan Yao; Hui Li; Li-Mei Lin; Jin-Rui Cai; Ya-Lu Zhan; Dong Wei; Shui-Yuan Chen; Da-Qin Chen; et al. (Chemical Engineering Journal, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Phenolic glycosides and indole alkaloids isolated from the roots and rhizomes of Clematis chinensis and their anti-inflammatory activity - Hai-Bing Jiang; Si-Yuan Shao; Ya-Zi Wei; Ming-Bao Lin; Shuai Li (Phytochemistry, 2023)

Numerical analysis of wake field and unsteady forces on submarine propeller with twisted rudders - Jin-ming Ye; Di Zhang; Zi-han Zheng; Wan-li Yang; Lin Ke (Ocean Engineering, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Behavior of 3D-printed HPC plates with FRP grid reinforcement under bending - Jun-Jie Zeng; Pei-Lin Li; Zi-Tong Yan; Jie-Kai Zhou; Wai-Meng Quach; Yan Zhuge (Engineering Structures, 2023)

Three new compounds from Anoectochilus roxburghii (Wall.) Lindl - Yan-Lin Bin; Shun-Zhi Liu; Ting-Ting Xie; Wen-Zheng Feng; Hao-Yang Li; Zi-Jia Ye; Zhi-Hao Dong; Ying-Kun Qiu (Natural Product Research, 2023)

Environmental exposure and ecological risk of perfluorinated substances (PFASs) in the Shaying River Basin, China - Ya-Hui Zhang; Ting-Ting Ding; Zi-Yan Huang; Hong-Yi Liang; Shi-Lin Du; Jin Zhang; Hui-Xian Li (Chemosphere, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

A bispecific nanobody with high sensitivity/efficiency for simultaneous determination of carbaryl and its metabolite 1-naphthol in the soil and rice samples - Min-ling Liu; Zi-jian Chen; Xiao-qing Huang; Hong Wang; Jin-li Zhao; Yu-dong Shen; Lin Luo; Xiao-wei Wen; Bruce Hammock; Zhen-lin Xu (Environmental Pollution, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Performance enhancement of proton exchange membrane fuel cells with bio-inspired gear-shaped flow channels - Yuzhi Ke; Baotong Zhang; Wei Yuan; Yafeng Bai; Yonghao Zhao; Zi'ang Liu; Zhenhe Lin; Xinze Li; Yangang Wang; Yong Tang (Chemical Engineering Journal, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

GABAergic Neurons in the Nucleus Accumbens are Involved in the General Anesthesia Effect of Propofol - Jing Yan; Bei-Ning Hang; Lin-Hui Ma; Jia-Tao Lin; Yue Zhou; Xin-Hao Jiao; Ying-Xuan Yuan; Ke-Jie Shao; Le-Meng Zhang; Qi Xue; Zi-Yi Li; Hong-Xing Zhang; et al. (Molecular Neurobiology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

In-situ gas flow separation between biochar and the heat carrier in a circulating fluidized bed reactor for biomass pyrolysis - Zheng-hao Yang; Zhen He; Xiang-gang Zhang; Xia Jiang; Zi-heng Jin; Jian-ping Li; Liang Ma; Hua-lin Wang; Yu-long Chang (Chemical Engineering Journal, 2023)

A one- and three-dimensional coupled model and simulation investigation for the large-scale oil-heating type Mg-based hydrogen storage tank - Xi Lin; Cheng-long Yin; Li Ren; Yinghui Li; Zi Li; Qiuyu Zhang; Zhigang Hu; Jianxin Zou (Chemical Engineering Journal, 2023)

An extracellular matrix-inspired self-healing composite hydrogel for enhanced platelet-rich plasma-mediated chronic diabetic wound treatment - Ya Zhang; Zi-Li Wang; Ze-Peng Deng; Zi-Lin Wang; Fei Song; Li-Li Zhu (Carbohydrate Polymers, 2023)

Four organosulfur compounds from the seeds of Capsella bursa-pastoris and their anti-inflammatory activities - Zhen-Zhen Wei; Ti-Qiang Zhou; Zi-Ming Xia; Si-Fan Liu; Min Li; Guang-Jie Zhang; Ying Tian; Bin Li; Lin Wang (Natural Product Research, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

The AMPK-dependent inhibition of autophagy plays a crucial role in protecting photoreceptor from photooxidative injury - Yu-Lin Li; Tian-Zi Zhang; Li-Kun Han; Chang He; Yi-Ran Pan; Bin Fan; Guang-Yu Li (Journal of Photochemistry and Photobiology B: Biology, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Enhanced removal of Cr(VI) by polyethyleneimine-modified bamboo hydrochar - Zi-Le Chen; Yu-Nan Zhang; Jian-Zhong Guo; Lin Chen; Bing Li (Environmental Science and Pollution Research, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Navigating practical applications of food waste valorisation based on the effects of food waste origins and storage conditions - Jin-Hua Mou; Zi-Hao Qin; Yu-Feng Yang; Si-Fen Liu; Wei Yan; Lan Zheng; Ya-Hui Miao; Hong-Ye Li; Patrick Fickers; Carol Sze Ki Lin; Xiang Wang (Chemical Engineering Journal, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Exploring the interaction between agronomic practices and soil characteristics on the presence of antibiotic resistance genes in soil - Xiao-Ming Lu; Li-Bo Lu; Yu-Hang Lin; Zi-Yi Chen; Jia-Hao Chen (Applied Soil Ecology, 2023)

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Stelleratenoids A−F, macrocyclic daphnane orthoesters with anti-HIV activity from the roots of Stellera chamaejasme L. - Kang Ding; Zi-Yao Wu; Nuan Zhang; Jun He; Fan Zhang; Jing-Jing Wu; Hong-Jin Bai; Wei-Ku Zhang; Lin Li; Jie-Kun Xu (Phytochemistry, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Phenylpropanoids from the Nitraria tangutorum fruit as glycerol phosphate dehydrogenase inhibitors through in vitro, in silico and in vivo studies - Zhi-Xiang Liu; Lin-Lin Yuan; Nan Zhang; Min Zhao; Yue Li; Ming-Yue Zhao; Yu-Meng Wang; Zi-Zhuo Wang; Yang-Yang Zhang; Jin-Long Tian (Food Bioscience, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

X-ray diffraction and the symmetry of ultrathin crystalline materials between two-dimensional and three-dimensional crystals - Hengrui Ma; Qiaorong Jiang; Zi-Ang Nan; Gen Li; Yanyan Jia; Ruoxin Ning; Jia-Bao Ji; Zhenming Cao; Linzhe Lü; Huiqi Li; Sheng Dai; Haixin Lin; et al. (Science Bulletin, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Zircon constraints on gold enrichment in a high-silica porphyry, Yixingzhai region, north of the Trans-North China Orogen - Zi-Hao Wen; Lin Li; Daniel E. Harlov; Sheng-Rong Li (Lithos, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Glyphosate-induced autophagy inhibition results in hepatic steatosis via mediating epigenetic reprogramming of PPARα in roosters - Cai-Yu Lian; Sheng Wei; Zi-Fa Li; Shu-Hui Zhang; Zhen-Yong Wang; Lin Wang (Environmental Pollution, 2023)

Insight into tetrahydrofuran lignans from Isatis indigotica fortune with neuroprotective and acetylcholinesterase inhibitor activity - Yu-Fei Xi; Ming Bai; Xin Zhang; Zi-Lin Hou; Bin Lin; Guo-Dong Yao; Li-Li Lou; Xiao-Bo Wang; Shao-Jiang Song; Xiao-Xiao Huang (Phytochemistry, 2023)

Ultrapotassic enclaves in the Miocene adakitic granitoids, southern Tibet: Direct evidence for collision-related crust-mantle interaction and its implications - Chang-da Wu; Yuan-chuan Zheng; Bo Xu; Zeng-qian Hou; Peng Chai; Xin Li; Lin-yuan Zhang; Zi-xuan Wang; Lu Wang; Yang Shen (Lithos, 2023)

Environmental profiling microalgae-based eicosapentaenoic acid production along the technical advancement via life cycle assessment - Zi-Hao Qin; Xiaomeng Hu; Jin-Hua Mou; Guo-Hui He; Guang-Bin Ye; Hong-Ye Li; Shauhrat Singh Chopra; Liang Dong; Carol Sze Ki Lin; Xiang Wang (Journal of Cleaner Production, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Longer dry and wet spells alter the stochasticity of microbial community assembly in grassland soils - Lingjuan Li; Ivan Nijs; Hans De Boeck; Olga Vindušková; Simon Reynaert; Chase Donnelly; Lin Zi; Erik Verbruggen (Soil Biology and Biochemistry, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

ZIF-8-derived Cu, N co-doped carbon as a bifunctional cathode catalyst for enhanced performance of microbial fuel cell - Bi-Lin Lai; Hui-Xu Wei; Zi-Nuo Luo; Tong Zheng; Yi-Hui Lin; Zhao-Qing Liu; Nan Li (Science of The Total Environment, 2023)

How swimming style and schooling affect the hydrodynamics of two accelerating wavy hydrofoils - Zhonglu Lin; Amneet Pal Singh Bhalla; Boyce E. Griffith; Zi Sheng; Hongquan Li; Dongfang Liang; Yu Zhang (Ocean Engineering, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

How Frequently Will the Persistent Heavy Rainfall over the Middle and Lower Yangtze River Basin in Summer 2020 Happen under Global Warming? - Zi-An Ge; Lin Chen; Tim Li; Lu Wang (Advances in Atmospheric Sciences, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Two-stage Bayesian experimental design optimization for measuring soil–water characteristic curve - Shao-Lin Ding; Dian-Qing Li; Zi-Jun Cao; Wenqi Du (Bulletin of Engineering Geology and the Environment, 2022)

Evaluation of reference genes for normalization of mRNA and microRNA expression by RT-qPCR under different experimental conditions in Medicago ruthenica (L.) Ledeb. - Mao-Wei Guo; Lin Zhu; Hong-Yan Li; Zi-Nian Wu; Zhi-Yong Li; Jun Li (Genetic Resources and Crop Evolution, 2022)

Adenine base-editing-mediated exon skipping induces gene knockout in cultured pig cells - Xiang-xing Zhu; Jia-sheng Pan; Tao Lin; Ye-cheng Yang; Qiu-yan Huang; Shuai-peng Yang; Zi-xiao Qu; Zi-sheng Lin; Jian-cong Wen; Ai-fen Yan; Juan Feng; Lian Liu; et al. (Biotechnology Letters, 2022)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Efficiently immobilizing uranium (VI) by oxidized carbon foam - Hongliang Bao; Chunyu Xie; Ling Han; Zenghui Yue; Yuan Qian; Linjuan Zhang; Zi-Jian Li; Huangjie Lu; Jian Lin; Jian-Qiang Wang (Environmental Science and Pollution Research, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Population-based meta-analysis of chloroquine: informing chloroquine pharmacokinetics in COVID-19 patients - Xueting Yao; Xiaoyu Yan; Xiaohan Wang; Ting Cai; Shun Zhang; Cheng Cui; Xiaoxu Wang; Zhe Hou; Qi Liu; Haiyan Li; Jing Lin; Zi Xiong; et al. (European Journal of Clinical Pharmacology, 2021)
Aims Chloroquine (CQ) has been repurposed to treat coronavirus disease 2019 (COVID-19). Understanding the pharmacokinetics (PK) in COVID-19 patients is essential to study its exposure–efficacy/safety relationship and provide a basis for a possible dosing regimen optimization. Subject and methods In this study, we used a population-based meta-analysis approach to develop a population PK model to characterize the CQ PK in COVID-19 patients. An open-label, single-center study (ethical review approval number: PJ-NBEY-KY-2020-063-01) was conducted to assess the safety, efficacy, and pharmacokinetics of CQ in patients with COVID-19. The sparse PK data from 50 COVID-19 patients, receiving 500 mg CQ phosphate twice daily for 7 days, were combined with additional CQ PK data from 18 publications. Results A two-compartment model with first-order oral absorption and first-order elimination and an absorption lag best described the data. Absorption rate (ka) was estimated to be 0.559 h −1 , and a lag time of absorption (ALAG) was estimated to be 0.149 h. Apparent clearance (CL/F) and apparent central volume of distribution (V2/F) was 33.3 l/h and 3630 l. Apparent distribution clearance (Q/F) and volume of distribution of peripheral compartment (Q3/F) were 58.7 l/h and 5120 l. The simulated CQ concentration under five dosing regimens of CQ phosphate were within the safety margin (400 ng/ml). Conclusion Model-based simulation using PK parameters from the COVID-19 patients shows that the concentrations under the currently recommended dosing regimen are below the safety margin for side-effects, which suggests that these dosing regimens are generally safe. The derived population PK model should allow for the assessment of pharmacokinetics–pharmacodynamics (PK-PD) relationships for CQ when given alone or in combination with other agents to treat COVID-19.

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Genetic diversity analysis reveals new badnaviruses infecting banana in South China - Xue-Qin Rao; Zi-Lin Wu; Wan Wang; Lin Zhou; Jie Sun; Hua-Ping Li (Journal of Plant Pathology, 2020)

A study on the application of the distributed optical fiber sensing monitoring technology in the process of dismantling temporary tunnel shoring - Zi-Xiang Li; Gong-Yu Hou; Tao Hu; Tian-Ci Zhou; Hai-Lin Xiao (Arabian Journal of Geosciences, 2020)

Scorpion Venom Heat-Resistant Peptide is Neuroprotective against Cerebral Ischemia-Reperfusion Injury in Association with the NMDA-MAPK Pathway - Xu-Gang Wang; Dan-Dan Zhu; Na Li; Yue-Lin Huang; Ying-Zi Wang; Ting Zhang; Chen-Mei Wang; Bin Wang; Yan Peng; Bi-Ying Ge; Shao Li; Jie Zhao (Neuroscience Bulletin, 2020)

Dynamic patterns of circular and linear RNAs in maize hybrid and parental lines - Zi Luo; Jia Qian; Sijia Chen; Lin Li (Theoretical and Applied Genetics, 2020)

One-step generation of zebrafish carrying a conditional knockout-knockin visible switch via CRISPR/Cas9-mediated intron targeting - Jia Li; Hong-Yu Li; Shan-Ye Gu; Hua-Xing Zi; Lai Jiang; Jiu-Lin Du (Science China Life Sciences, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Circular RNAs exhibit extensive intraspecific variation in maize - Zi Luo; Linqian Han; Jia Qian; Lin Li (Planta, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Landslide integrated characteristics and susceptibility assessment in Rongxian county of Guangxi, China - Li-ping Liao; Ying-yan Zhu; Yan-lin Zhao; Hai-tao Wen; Yun-chuan Yang; Li-hua Chen; Shao-kun Ma; Ying-zi Xu (Journal of Mountain Science, 2019)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

A unique genetic lineage at the southern coast of China in the agar-producing Gracilaria vermiculophylla (Gracilariales, Florideophyceae) - Zi-Min Hu; Ruo-Yu Liu; Jie Zhang; De-Lin Duan; Gao-Ge Wang; Wen-Hong Li (Algae, 2018)

Effects of Zinc Supplementation During In Vitro Maturation on Meiotic Maturation of Oocytes and Developmental Capacity in Yak - Xianrong Xiong; Daoliang Lan; Jian Li; Yaqiu Lin; Xiangdong Zi (Biological Trace Element Research, 2018)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

An Assessment of Genetic Diversity of Yield-Related Traits of Saccharum spontaneum from Yunnan Province, China - Chaohua Xu; Huosheng Su; Hongbo Liu; Xin Lu; Xujuan Li; Chunjia Li; Xiuqin Lin; Jun Mao; Qiuyan Zi; XinLong Liu (Sugar Tech, 2017)

Effects of genetic variants of the bovine WNT8A gene on nine important growth traits in beef cattle - Yong-Zhen Huang; Yong Zou; Qing Lin; Hua He; Li Zheng; Zi-Jing Zhang; Yong-Long Dang; Chu-Zhao Lei; Xian-Yong Lan; Xing-Shan Qi; Hong Chen (Journal of Genetics, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Metformin Improves Functional Recovery After Spinal Cord Injury via Autophagy Flux Stimulation - Di Zhang; Jun Xuan; Bin-bin Zheng; Yu-long Zhou; Yan Lin; Yao-sen Wu; Yi-fei Zhou; Yi-xing Huang; Quan Wang; Li-yan Shen; Cong Mao; Yan Wu; et al. (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

PGRN Is Associated with Late-Onset Alzheimer’s Disease: a Case–Control Replication Study and Meta-analysis - Hui-Min Xu; Lin Tan; Yu Wan; Meng-Shan Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Oceanic currents drove population genetic connectivity of the brown alga Sargassum thunbergii in the north‐west Pacific - Jing‐Jing Li; Zi‐Min Hu; Xu Gao; Zhong‐Min Sun; Han‐Gil Choi; De‐Lin Duan; Hikaru Endo (Journal of Biogeography, 2017)
Aim Oceanic currents are among the most pervasive hydrodynamic features in shaping community dynamics, population connectivity and phylogeographical structure of intertidal species. Here, we test whether population structure and biogeographical gradients of genetic diversity in the brown alga Sargassum thunbergii are correlated with oceanic currents in the north‐west Pacific ( NWP ). Location North‐west Pacific (25.07°N–43.36°N). Methods Nuclear internal transcribed spacer‐2 and mitochondrial cox 3 sequences were obtained from 835 and 810 individuals of S. thunbergii respectively. Parsimony networks and phylogenetic trees (maximum parsimony and Bayesian inference) were constructed to evaluate phylogeographical structure. Pairwise F ST estimates and analyses of molecular variance ( AMOVA ) at various hierarchical levels (latitude, longitude, marine provinces, biogeographical basins and zoogeographical zones) were conducted to elucidate population genetic differentiation. migrate software was used to estimate the number of migrants between adjacent populations. Results Several lines of evidence indicate that S. thunbergii is characterized by shallow population structure. Geographical distances do not correlate with population pairwise genetic differentiations. The corridor/stepping‐stone model‐based coalescent analyses reveal high levels of asymmetric gene flow among S. thunbergii populations, with the numbers of migrants largely corresponding to the directions of oceanic current systems in the NWP . Genetic signatures also indicate that Jeju Island, Korea might act as a transition zone for dispersal of S. thunbergii in the NWP driven by the Kuroshio Current, thus facilitating subsequent transportation northward into the Sea of Japan and the Yellow‐Bohai Sea. Main conclusions Population genetic homogeneity in S. thunbergii was mainly structured by oceanic currents rather than palaeoclimatic events. Our study illustrates an important phylogeographical case of how coastal hydrodynamic factors contributed to population connectivity and geographical shifts of genetic diversity for marine organisms without a pelagic stage.

Dissipation of excess excitation energy of the needle leaves in Pinus trees during cold winters - AO Zhang; Zhen-Hai Cui; Jia-Lin Yu; Zi-Ling Hu; Rui Ding; Da-Ming Ren; Li-Jun Zhang (International Journal of Biometeorology, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Co-expression of MtDREB1C and RcXET Enhances Stress Tolerance of Transgenic China Rose (Rosa chinensis Jacq.) - Ji-Ren Chen; Yan-Bin Chen; Monika Ziemiańska; Rong Liu; Zi-Niu Deng; Irena Niedźwiecka-Filipiak; Yan-Lin Li; Jin-Xia Jiao; Xing-Yao Xiong (Journal of Plant Growth Regulation, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Distinct subcellular localization and potential role of LINE1-ORF1P in meiotic oocytes - Yi-Bo Luo; Li Zhang; Zi-Li Lin; Jun-Yu Ma; Jialin Jia; Suk Namgoong; Qing-Yuan Sun (Histochemistry and Cell Biology, 2016)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Phylogeographic structure and deep lineage diversification of the red alga Chondrus ocellatus Holmes in the Northwest Pacific - Zi‐Min Hu; Jing‐Jing Li; Zhong‐Min Sun; Jung‐Hyun Oak; Jie Zhang; Pablo Fresia; W. Stewart Grant; De‐Lin Duan (Molecular Ecology, 2015)
A major goal of phylogeographic analysis using molecular markers is to understand the ecological and historical variables that influence genetic diversity within a species. Here, we used sequences of the mitochondrial Cox 1 gene and nuclear internal transcribed spacer to reconstruct its phylogeography and demographic history of the intertidal red seaweed Chondrus ocellatus over most of its geographical range in the Northwest Pacific. We found three deeply separated lineages A, B and C, which diverged from one another in the early Pliocene–late Miocene ( c . 4.5–7.7 Ma). The remarkably deep divergences, both within and between lineages, appear to have resulted from ancient isolations, accelerated by random drift and limited genetic exchange between regions. The disjunct distributions of lineages A and C along the coasts of Japan may reflect divergence during isolation in scattered refugia. The distribution of lineage B, from the South China Sea to the Korean Peninsula, appears to reflect postglacial recolonizations of coastal habitats. These three lineages do not coincide with the three documented morphological formae in C. ocellatus , suggesting that additional cryptic species may exist in this taxon. Our study illustrates the interaction of environmental variability and demographic processes in producing lineage diversification in an intertidal seaweed and highlights the importance of phylogeographic approaches for discovering cryptic marine biodiversity.

A fast-convergence POCS seismic denoising and reconstruction method - Zi-Jian Ge; Jing-Ye Li; Shu-Lin Pan; Xiao-Hong Chen (Applied Geophysics, 2015)

Genetic data from the red alga Palmaria palmata reveal a mid‐Pleistocene deep genetic split in the North Atlantic - Jing‐Jing Li; Zi‐Min Hu; De‐Lin Duan (Journal of Biogeography, 2015)
Aim We examined the biogeographical divergence, population‐level genetic differentiation and historical genetic exchange of the red macroalga Palmaria palmata in order to test whether populations on opposite sides of the North Atlantic underwent different demographic histories. Location North Atlantic rocky intertidal zones between c . 42 and 65° N. Methods We compiled mitochondrial (mt DNA ) cox 2–3 and plastid rpl 12– rps 31– rpl 9 sequences from 333 and 310 individuals of P. palmata , respectively. Median‐joining networks were constructed to evaluate the genetic relationships among haplotypes. Pairwise genetic differentiation ( F ST ) was calculated to elucidate population genetic structure. Spatial analysis of molecular variance was used to define genetic differentiation between groups. Extended Bayesian skyline plots and IM a 2 were used to estimate historical demography, genetic divergence and gene flow between regions. Results The mt DNA cox 2–3 haplotype network and phylogenetic trees consistently showed that North Atlantic P. palmata divided into two genetic lineages in association with mid‐Pleistocene (0.126–0.781 Ma) climate change. The demographic expansion time for European populations was c . 0.169–0.320 Ma. North American populations underwent demographic expansion c . 0.400 Ma but, for the populations in the Bay of Fundy, a sharp population‐size contraction happened c . 0.013–0.160 Ma. IM a 2 analysis revealed no gene flow between the European and North American coasts. Main conclusions Our results suggest significant genetic differentiation in P. palmata both at a trans‐Atlantic continental scale and at a European basin scale, and that multiple glacial refugia may have existed for this species. Long‐term isolation within the Atlantic may have contributed greatly to structuring the population‐genetic differentiation of P. palmata . Our results also stress the importance of combining different gene markers to understand the phylogeographical history and genetic structure of marine biota.

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

The wheat NHX antiporter gene TaNHX2 confers salt tolerance in transgenic alfalfa by increasing the retention capacity of intracellular potassium - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Hui-Cong Li; Xiu-Lin Guo; Guo-Liang Li (Plant Molecular Biology, 2015)

Effects of boron toxicity on root and leaf anatomy in two Citrus species differing in boron tolerance - Jing-Hao Huang; Zi-Jian Cai; Shou-Xing Wen; Peng Guo; Xin Ye; Gui-Zhu Lin; Li-Song Chen (Trees, 2014)

Prediction of protein structural classes based on feature selection technique - Hui Ding; Hao Lin; Wei Chen; Zi-Qiang Li; Feng-Biao Guo; Jian Huang; Nini Rao (Interdisciplinary Sciences: Computational Life Sciences, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Polycyclic aromatic hydrocarbons in water, sediment and soil of the Songhua River Basin, China - Wan-Li Ma; Li-Yan Liu; Hong Qi; Zi-Feng Zhang; Wei-Wei Song; Ji-Min Shen; Zhong-Lin Chen; Nan-Qi Ren; Josey Grabuski; Yi-Fan Li (Environmental Monitoring and Assessment, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Pharmacophore modeling, virtual screening, and molecular docking studies for discovery of novel Carbonic anhydrase IX inhibitors - Chun-Lin Lu; Lu Zhou; Zi-Cheng Li; Xiang Gao; Wei Zhang (Medicinal Chemistry Research, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Positive allelopathic stimulation and underlying molecular mechanism of achyranthe under continuous monoculture - Zhen-Fang Li; Zi-Guan Zhang; Dong-Feng Xie; Lin-Quan Dai; Lan-Fang Zhu; Ji Li; Zong-Quan Liu; Yan-Qiu Yang; Lin-Kun Wu; Mu-Ji Huang; Zhong-Yi Zhang; Wen-Xiong Lin (Acta Physiologiae Plantarum, 2011)

The complete mitochondrial genomes of three cestode species of Taenia infecting animals and humans - Guo-Hua Liu; Rui-Qing Lin; Ming-Wei Li; Wei Liu; Yi Liu; Zi-Guo Yuan; Hui-Qun Song; Guang-Hui Zhao; Kou-Xing Zhang; Xing-Quan Zhu (Molecular Biology Reports, 2011)

Enhancement of salt tolerance in alfalfa transformed with the gene encoding for betaine aldehyde dehydrogenase - Zi-Hui Liu; Hong-Mei Zhang; Guo-Liang Li; Xiu-Lin Guo; Shou-Yi Chen; Gui-Bo Liu; Yan-Min Zhang (Euphytica, 2011)

Production, purification and characterization of a thermostable laccase from a tropical white-rot fungus - Li-Qiong Guo; Shuo-Xin Lin; Xiao-Bing Zheng; Zi-Rou Huang; Jun-Fang Lin (World Journal of Microbiology and Biotechnology, 2011)

Blocking NF-κB and Akt by Hsp90 inhibition sensitizes Smac mimetic compound 3-induced extrinsic apoptosis pathway and results in synergistic cancer cell death - Lang Bai; Shanling Xu; Wenshu Chen; Zi Li; Xia Wang; Hong Tang; Yong Lin (Apoptosis, 2011)

Analysis of two sequence variants in peroxisome proliferator activated receptor gamma gene in Tajik population at high altitudes and Han population at low altitudes in China - Xiao-Ling Liu; Feng-Lin Zhang; Zhi-Yong Zhou; Hua-Lu Zhao; Guo-Min Shen; Wu-Yun Baohan; Zi-Yuan Duan; Wei Li; Jun-Wu Zhang (Molecular Biology Reports, 2010)

Activity of the Antimicrobial Peptide and Thanatin Analog S-thanatin on Clinical Isolates of Klebsiella pneumoniae Resistant to Conventional Antibiotics with Different Structures - Guo-Qiu Wu; Jia-Xuan Ding; Lin-Xian Li; Hai-liang Wang; Rui Zhao; Zi-Long Shen (Current Microbiology, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Evolutionary and functional study of the CDPK gene family in wheat (Triticum aestivum L.) - Ai-Li Li; Yuan-Fang Zhu; Xiao-Mei Tan; Xiang Wang; Bo Wei; Han-Zi Guo; Zeng-Lin Zhang; Xiao-Bo Chen; Guang-Yao Zhao; Xiu-Ying Kong; Ji-Zeng Jia; Long Mao (Plant Molecular Biology, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Mineralogical and geochemical study of a newly discovered mafic granulite, northwest China: Implications for tectonic evolution of the Altay Orogenic Belt - Han‐Lin Chen; Zi‐Long Li; Shu‐Feng Yang; Chuan‐Wan Dong; Wen‐Jiao Xiao; Yoshiaki Tainosho (Island Arc, 2006)
A mafic granulite body was newly discovered in the Altay Orogenic Belt, northwest China. The rocks comprise a suite of coarse‐grained and fine‐grained granulites. Orthopyroxenes (hypersthenes) in the rocks have high X Mg and low Al 2 O 3 contents, whereas clinopyroxenes have low TiO 2 and Al 2 O 3 contents. Amphiboles and biotites have a high Mg/(Mg + Fe 2+ ) ratio and low contents of F and Cl. The peak metamorphic pressure–temperature (P–T) conditions are estimated as 750–780°C and 6–7 kbar, and retrograde P–T conditions are in the range of 590–620°C and 2.3–3.7 kbar, indicating significant decompression. Metamorphic reactions and P–T estimates define a clockwise P–T path. Geochemically, the rocks are high in Mg/(Mg + Fe) and Al 2 O 3 , depleted in U, Th, K and Rb, and characterized by light rare earth element enrichment and a weak positive Eu anomaly. The Altay mafic granulite shows depleted Nb, P and Ti contents in the mid‐oceanic ridge basalt normalized spider diagram. The geochemical characteristics suggest that the protolith of the Altay mafic granulite was calc‐alkaline basalt and andesite with an island‐arc affinity. The rock has a high 143 Nd/ 144 Nd ratio with ɛNd(0) > 0, indicating derivation from a mantle‐depleted source. In the present study, a two‐stage model for the evolution of the Altay mafic granulite is proposed: an early stage in which calc‐alkaline basalt and andesite with island‐arc affinity were subducted into a deeper level of the crust and subjected to granulite‐facies metamorphism generating the mafic granulite, followed by the later stage exhumation of the system into the upper crust by the late Paleozoic thrusting.